If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7y + 1.4 + 1.6y + 1.3y + -2 = 0 Reorder the terms: 1.4 + -2 + -7y + 1.6y + 1.3y = 0 Combine like terms: 1.4 + -2 = -0.6 -0.6 + -7y + 1.6y + 1.3y = 0 Combine like terms: -7y + 1.6y = -5.4y -0.6 + -5.4y + 1.3y = 0 Combine like terms: -5.4y + 1.3y = -4.1y -0.6 + -4.1y = 0 Solving -0.6 + -4.1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.6' to each side of the equation. -0.6 + 0.6 + -4.1y = 0 + 0.6 Combine like terms: -0.6 + 0.6 = 0.0 0.0 + -4.1y = 0 + 0.6 -4.1y = 0 + 0.6 Combine like terms: 0 + 0.6 = 0.6 -4.1y = 0.6 Divide each side by '-4.1'. y = -0.1463414634 Simplifying y = -0.1463414634
| 7m+3/4 | | (1+x)(5x+8)=0 | | 1525200=0.5*9840*x^2 | | Y+2.6=5.36 | | -3(u-4x-6)= | | 639600=0.5*9840*x^2 | | 6f+3-12f=-3 | | 6f+3-12f=3 | | 2(-3c+6)=6 | | (3c)(2^4c^-2d^3)/(8n^2c^-4d^-2)^-3 | | 4/5/1/2 | | -3x+0.1+2.4x-2.7-3= | | X(2x^2+9x-56)(3x+10)=0 | | 25m^2-16/19 | | x^2/2-1+x=-1 | | 5(3x+4)-2=48 | | (x-4)(x+3)=6(x+1) | | 2x-5x-2=0 | | -25=4a-45 | | 2w+L=5 | | -6+2a=2 | | (x+3)(x)=8 | | (3x)(x)=8 | | 10=-2y | | (2x+5)+(-3x+1)= | | 5(x-3)-7x=4(x-3)+9 | | -4M+2+6M-8=-2 | | 4x^2+1-4x=0 | | 9(3x-4)=72 | | 4y^2+24y+32=0 | | 1/3-7=-2 | | 9x=909 |